Principalsï¿½ e-leadership practices, teachersï¿½ computer-mediated communication competence, school virtual learning culture and teachersï¿½ attitudes toward Frog VLE in Klang / Oh Siew Pei - Oh , Siew Pei (2017)
Malaysia Education Blueprint 2013-2025 was introduced to develop a new education vision in Malaysiaï¿½s education system. In accordance with the governmentï¿½s vision of giving quality internet-enabled education for all, Ministry of Education Malaysia (MOE) had initiated a project known as 1BestariNet to equip all 10,000 schools in Malaysia with the Internet-based Virtual Learning Environment (Frog VLE). The usages of Frog VLE in all Malaysian schools are under tremendous pressure to improve. Principalsï¿½ e-leadership, teachersï¿½ CMC competence, school virtual learning culture, and teachersï¿½ attitude toward using Frog VLE is a research avenue which must be extensively explored with the anticipation that the findings will enhance existing practices or increase the usage of Frog VLE. Specifically, this proposed study examined the relationship between secondary school principalsï¿½ e-leadership practices with teachersï¿½ attitude toward using the Frog VLE in the Klang district or it is mediated by teachersï¿½ computer-mediated communication competence and school virtual learning culture. Teachersï¿½ demographic characteristics were chosen as moderating variables. This is a non-experimental research using a cross-sectional survey technique through administration of questionnaire. A total of 454 teachers from 34 daily public secondary schools in Klang district were randomly selected to participate in this study and a total of 383 subjects responded to the study with a response rate of 84.4%. Based on Krejcie & Morganï¿½s (1970), the minimum number of respondents needed for this study at 95% confidence level is 351 teachers. Hence, 351 questionnaires randomly selected was first analyzed for descriptive statistics in term of mean and standard deviation followed by inferential statistics such as Spearmanï¿½s -rho tests which help to identify the relationship between variables. Structural equation modelling (SEM) procedures with Smart PLS 2 is used to examine the mediation and moderation model proposed. Results indicated that teachers in the Klang district secondary schools showed medium level of attitude and CMC competence toward using Frog VLE. Besides, teachers perceived that their principals demonstrated medium level of e-leadership practices and perceived that their school demonstrated medium level of school virtual learning culture toward using Frog VLE. The findings confirmed that there is statistically significant positive correlation between principal e-leadership practices, teacher CMC competence, school virtual learning culture, and teacher attitude toward using Frog VLE. This study concluded that there is a full mediating effect of teacher CMC competence and partial mediating effect of school virtual learning culture on the relationship between principal e-leadership practices and teacher attitude toward using Frog VLE. Teacher demographic characteristics such as gender, age, computer experience and teaching experience are not the moderators. This current study has numerous implications and contributions to the body of knowledge on technology integration and pedagogical innovations. The findings of this study could be compared and contrasted with similar studies in other regions and countries and the mediation model established could be further tested and verified.